Illocutionary Acts in President Joe Biden’s Speech - Atusaadah, Maghfirah; Zuindra, Zuindra (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2022)
Abstra ct -- This article aimed to specify  the kinds of illocutionary acts and defined the existence of illocutionary acts and their meaning in a speech to discover the outcomes of the maximum dominant kinds of illocutionary acts in President Joe Biden's speech. The research method used in completing this research becomes the descriptive qualitative method. In studying the data, the theory of Searle (1979) becomes used to determine the illocutionary act category of the speaker utterances. The tool used in collecting and analyzing the information was the speech video of President Joe Biden and the script acquired from the internet. The result of this research confirmed that there was 41 information and the researcher observed five types of the illocutionary act by using Searle’s theory in President Joe Biden’s speech which are assertive, directive, commisive, expressive, and declarative. The most dominant was assertive illocutionary act that implies stating, announcing, reporting, assertion, claiming, telling, informing, assuring, complaining, and concluding .   Keywords : P ragmatics ; s peech a ct; illocutionary a ct; s peech